The Effect of Dental Health Education with Video Media on Knowledge and Interest Odontectomy Procedures - Renaningtyas, Kun Ari Niken Ayu; A`yun, Quroti; Risnawati, Dewi; Haryani4, Wiworo (Jurnal Kesehatan Gigi, 2025)
In Indonesia the number of dental and oral problems reaches 57.6%. The results of a preliminary study at a dental practice in Sumberadi Sleman found that 60% were not interested in carrying out an odontectomy. Odontectomy is a method of extracting or removing teeth that cannot grow or grow partially. The influence of dental health education using video media on knowledge and interest in odontectomy procedures is known. This research design is quasi-experimental with a Non-Equivalent Control Group design. The research was conducted in February 2024, the research population was patients at dental practices in Sumberadi Sleman with a sample of 64 respondents. Data were collected using a knowledge and interest questionnaire for odontectomy procedures. Data analysis used the Wilcoxon Test and Mann Whitney Test.The results of the research showed that the frequency of knowledge level was mostly good criteria (93.8%) and the highest frequency of interest in odontectomy (93.8%). The Wilcoxon test showed that there was a significant difference before and after being given education about odontectomy using video media with a p value 0.05. The results of the Mann Whitney test showed that there was a significant difference between promotion using video media and lecture media on knowledge and interest in odontectomy procedures, with a p value 0.05.Education about odontectomy using media influential videos to increase knowledge and interest in odontectomy procedures.